PENGARUH PENGETAHUAN DAN KELELAHAN KERJA TERHADAP UNSAFE ACTION PADA PEKERJA OPERASIONAL KALLA TRANSPORT & LOGISTIK - Labibah, Iffat Nurjihan; Amelia AP, A. Rizki; Muchlis, Nurmiati (J-KESMAS: Jurnal Kesehatan Masyarakat, 2023)
Unsafe behaviors can endanger people or workers and are caused by internal factors such as worker knowledge or fatigue. The study used a quantitative method with a cross-sectional approach with 51 respondents. Data were collected by questionnaire and analyzed using univariate and bivariate tests with a confidence level of α = 0.05. The binary logistic regression test results show that work fatigue is the variable that significantly influences risky behavior (p-value 0.019). The Exp(B) for job fatigue is 5,348, indicating that fatigue has a five times greater impact on risky behavior than knowledge does.